ChemInform Abstract: 25th Anniversary Article: Semiconductor Nanowires — Synthesis, Characterization, and Applications. Issue 24 (2nd June 2014) - Dasgupta, Neil P.; Sun, Jianwei; Liu, Chong; Brittman, Sarah; Andrews, Sean C.; Lim, Jongwoo; Gao, Hanwei; Yan, Ruoxue; Yang, Peidong
Abstract Review: 350 refs.